An analysis of export performance and economic growth of Malaysia using co-integration and error correction model - Sulaiman, Muna; Md Saad, Norma (2009)
This paper aims to test the relationship between export and economic growth in the Malaysian economy from 1960 to 2005. Combining production function, and international trade and development theories, a five variable model is specified and estimated by using cointegration tests and error correction model. Multivariate cointegration results revealed that there exists a single cointegrating vector in the estimated system. This means that these variables are linked together in achieving their steady state equilibrium in the long run. From the estimation of the specified model, we reported that there is a positive relationship between export and economic growth in the long run and short run at 5 percent significance level in the Malaysian economy. Besides, our results suggest that capital has positive impacts on economic growth in the short-term and long-term but labor has an impact on economic growth only in the long run. For imports, it is proven that it has a negative relationship with economic growth.